(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
his article explores the semantic functions of speech sounds and phonemes and their critical role in distinguishing meaning in language. Phonemes, as the smallest units of sound that differentiate words, provide the basis for semantic differentiation—subtle shifts in sound can alter meaning, as in minimal pairs like "bat" and "pat." The article also discusses the influence of suprasegmental features (e.g., pitch, stress, and intonation) on meaning, highlighting how they add emotional and contextual layers to language. In addition, the concept of phonesthemes illustrates how certain sound clusters may carry semantic associations across different words (e.g., "gl-" in "glow" and "glitter," often related to light). The piece further contrasts phoneme functions across languages, noting how certain languages rely more on specific phonetic distinctions than others, while acknowledging the influence of morpheme-phoneme interactions and language evolution on meaning. This analysis enriches our understanding of how languages use sound to communicate complex meanings and emotions.